Optical Molecular Imaging of Inflammatory Cells in Interventional Medicine–An Emerging Strategy - Birch, Gavin P.; Campbell, Thane; Bradley, Mark; Dhaliwal, Kevin (Frontiers in Oncology, 2019)
The optical molecular imaging of inflammation is an emerging strategy for interventional medicine and diagnostics. The host’s inflammatory response and adaptation to acute and chronic diseases provides unique signatures that have the potential to guide interventions. Thus there are emerging a suite of molecular imaging and sensing approaches for a variety of targets in this area. This review will focus on two key cellular orchestrators that dominate this area, neutrophils and macrophages, with recent developments in molecular probes and approaches discussed.